Effect On Alpha Hemoglobin Chain Expression In K562 Cell Line - SH Alizadeh; S Kaviani; M Soleimani; AA Pourfathollah; N Amirizadeh; F Kouhkan; S Abroun; M Noruzinia (Tehran University of Medical Sciences, 2011)
Background and Aim: MicroRNAs (miRNA) are small noncoding RNA molecules that transcribed by RNA polymerase II. After biogenesis, these molecules act by incorporation into the RNA-induced silencing complex (RISC). MiRNAs are involved in multiple physiological and pathological processes such as proliferation, differentiation, apoptosis and cancer. Recently several studies reported down regulation of mir-150 during erythropoesis. Since hemoglobin expression is valuable indicator of erythroid differentiation we evaluated the mir-150 downregulation effect on alpha chain expression by Quantitative RT-PCR. Materials and Methods: K562cells were grown in RPMI1640 in standard condition. K562 cells were transfected by microRNA 150 Inhibitor using transfection kit .Mir-150 downregulation was confirmed by miRNA Real time PCR, followed by Q-RT-PCR to investigate the alpha chain expression changes. Results: By relative QRT-PCR the alpha chain expression was increased 10 folds in comparison to untransfected and scramble cells. Furthermore, the differences were statistically significant (P<0.05) Conclusion: Elevation of alpha chain expression in our study showed that mir-150 downregulation has a crucial role in erythroid differentiation and can introduce as a novel marker in alpha thalassemia. Further researches to find out the detail mechanism and miRNAs genes target could improve our knowledge about miRNAs potential in management of diseases and their applications in gene therapy and regenerative medicine.